Energy Consumption and Human Development in South Africa: Empirical Evidence from Disaggregated Data - Musakwa, Mercy T.; Odhiambo, Nicholas M. (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
This study investigated the impact of energy consumption on human development in South Africa, using annual data from 1990 to 2019. The study used disaggregated data on energy measures namely: oil products consumption; electricity consumption; renewable energy consumption; natural gas; coal and lignite; and total energy consumption at an aggregate level. Human Development Index (HDI) was used as a measure of human development. By employing autoregressive distributed lag bounds test to cointegration and error correction model, the study found the impact of energy consumption on human development to be positive in the short run when renewable energy was used as a proxy, but insignificant in the long run. When oil products, natural gas and total energy were used as proxies for energy, a negative impact was confirmed in the short run, while an insignificant impact was confirmed in the long run. When electricity, coal and lignite were used as proxies for energy, an insignificant impact was confirmed, irrespective of the time frame considered. The results revealed that the positive impact of renewable energy on human development is not big enough to offset the negative impact of other energy sources. This suggests that South Africa has to continue to expand renewable energy if a positive impact of energy on human development is to be realized.